(3MGTjI OOg CafOi Ydi TQM JUQja GdYRis - (3OOg CafOi GceGd GdOjf OOg NdjaIs; (3GdSYO GdJaJGRGfj , SYO GdOjf eSYhO Hf YeQ Hf YHO Gddg GdJaJGRGfj,J (B793 (3g` s
(3ChdgG (B:s
(3bhdg HSe Gddg GdQMef GdQMje Cbhd GHJOGA HGdJSejI s
(3BNQgG (B:s
(3hWYe GdTF Ci Ccd hPGb JeJ s
(3GdfSNI HgG MhGTs
(3YdjgG Jedcs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B219 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B228 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B430s
Keywords: (3GdUQas